Effect of Moderate and Severe Persistent Hyperglycemia on Outcomes in Patients With Intracerebral Hemorrhage. Issue 4 (30th November 2021) - Qureshi, Adnan I.; Huang, Wei; Lobanova, Iryna; Chandrasekaran, Premkumar N.; Hanley, Daniel F.; Hsu, Chung Y.; Martin, Renee H.; Steiner, Thorsten; Suarez, Jose I.; Yamamoto, Haruko; Toyoda, Kazunori
Abstract : Background: We evaluated the effect of persistent hyperglycemia on outcomes in 1000 patients with intracerebral hemorrhage enrolled within 4.5 hours of symptom onset. Methods: We defined moderate and severe hyperglycemia based on serum glucose levels ≥140 mg/dL—<180 and ≥180 mg/dL, respectively, measured at baseline, 24, 48, and 72 hours. Persistent hyperglycemia was defined by 2 consecutive (24 hours apart) serum glucose levels. We evaluated the relationship between moderate and severe hyperglycemia and death or disability (defined by modified Rankin Scale score of 4–6) at 90 days in the overall cohort and in groups defined by preexisting diabetes. Results: In the multivariate analysis, both moderate (odds ratio, 1.8 [95% CI, 1.1–2.8]) and severe (odds ratio, 1.8 [95% CI, 1.2–2.7]) hyperglycemia were associated with higher 90-day death or disability after adjusting for Glasgow Coma Scale score, hematoma volume, presence or absence of intraventricular hemorrhage, hyperlipidemia, cigarette smoking, and hypertension (no interaction between hyperglycemia and preexisting diabetes, P =0.996). Among the patients without preexisting diabetes, both moderate (odds ratio, 1.8 [95% CI, 1.0–3.2]) and severe (odds ratio, 2.0 [95% CI, 1.1–3.7]) hyperglycemia were associated with 90-day death or disability after adjusting for above mentioned potential confounders. Among the patients with preexisting diabetes, moderate and severe hyperglycemia were not associated with 90-day death or disability. Conclusions: Persistent hyperglycemia, either moderate or severe, increased the risk of death or disability in nondiabetic patients with intracerebral hemorrhage. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01176565.